Prototype Monitoring Kantung Cairan Infus Berbasis Internet Of Things (IoT) - Mahpuz Mahpuz; Hariman Bahtiar; Muhamad Sadali; Feni Kurniawan (Fakultas Teknik Universitas Hamzanwadi, 2023)
Infusion or intravenous therapy is the introduction of a fluid or drug into the body through the intravenous route at a constant rate over a certain period of time and is carried out continuously as a treatment measure. The extensive hospital conditions, coupled with the condition of different patients, infusion changes are often a common problem, such as infusion fluids that have run out but have not been replaced, which is a problem when patients have to be hospitalized. To overcome this problem, the Internet of Things (IoT)-Based Infusion Bag Monitoring Prototype is a prototype to assist medical personnel in monitoring the volume of fluid in the infusion bag remotely so as not to constantly check the patient's infusion in each room. The purpose of this study is to create an infusion bag weight monitoring device to monitor the volume of infusion fluid for each inpatient based on the internet of things (IoT) by utilizing the workings of a load cell sensor that functions to read infusion weight. As a microcontroller unit, it uses ESP8266 as a data uploader to the internet so that medical personnel can monitor the condition of the infusion bag for each patient through hospital devices, both computers and smartphones with the Blynk application.